Emerging Technologies: the digital revolution around and above us - Lisi, Marco (GEOmedia, 2017)
Ubiquitous Localization and Timing, Ubiquitous Sensing, Ubiquitous Connectivity, 3D Digital Modeling: these four main technological trends are triggering an epochal transition in the history of mankind, characterized by an increasing predominance of services in our economy. These emerging technologies will cause radical transformations of our society: it is an entirely New World we are facing.